Understanding Transferable Supply Chain Lessons and Practices to a “High-Tech” Industry Using Guidelines from a Primary Sector Industry: A Case Study in the Food Industry Supply Chain - Adrian E. Coronado Mondragon; Christian E. Coronado Mondragon; Etienne S. Coronado (The Scientific World Journal)
Flexibility and innovation at creating shapes, adapting processes, and modifying materials characterize composites materials, a “high-tech” industry. However, the absence of standard manufacturing processes and the selection of materials with defined properties hinder the configuration of the composites materials supply chain. An interesting alternative for a “high-tech” industry such as composite materials would be to review supply chain lessons and practices in “low-tech” industries such as food. The main motivation of this study is to identify lessons and practices that comprise innovations in the supply chain of a firm in a perceived “low-tech” industry that can be used to provide guidelines in the design of the supply chain of a “high-tech” industry, in this case composite materials. This work uses the case study/site visit with analogy methodology to collect data from a Spanish leading producer of fresh fruit juice which is sold in major European markets and makes use of a cold chain. The study highlights supply base management and visibility/traceability as two elements of the supply chain in a “low-tech” industry that can provide guidelines that can be used in the configuration of the supply chain of the composite materials industry.